Impact of Current Collector Design and Cooling Topology on Fast Charging of Cylindrical Lithium-Ion Batteries. (1st December 2022) - Frank, Alexander; Sturm, Johannes; Steinhardt, Marco; Rheinfeld, Alexander; Jossen, Andreas
Abstract : The 18 650 and 21 700 cell format are state of the art for high-energy cylindrical lithium-ion batteries, while Tesla proposed the new 4680 format with a continuous "tabless" design as the choice for electric vehicle applications. Using an experimentally validated multidimensional multiphysics model describing a high energy NMC811/Si-C cylindrical lithium-ion battery, the effects of tabless design and cooling topologies are evaluated for 18 650, 21 700, and 4680 cell formats under varying charging protocols. Mantle cooling is found to be the most efficient cooling topology for a segmented tab design, whereas tab cooling performs equally well for tabless cells and achieves better performance for the 4680 format. By massively reducing polarization drops (approx. 250 mV at 3C) and heat generation inside the current collectors (up to 99%), the tabless design increases cell homogeneity and enables format-independent scalability of fast-charging performance with a tab-cooling topology. In addition, the 0 to 0.8 SoC charge time can be reduced by 4 to 10 min compared to cells with a segmented tab design, resulting in 16.2 min for the 18 650 and 21 700, and 16.5 min for the larger 4680 cell format.